c-Jun Amino Terminal Kinase Signaling Promotes Aristolochic Acid-Induced Acute Kidney Injury - Yang, Fan; Ozols, Elyce; Ma, Frank Y.; Leong, Khai Gene; Tesch, Greg H.; Jiang, Xiaoyun; Nikolic-Paterson, David J. (Frontiers in Physiology, 2021)
Aristolochic acid (AA) is a toxin that damages tubular epithelial cells of the kidney and is the cause of Balkan Nephropathy and Chinese Herb Nephropathy. Exposure of cultured tubular epithelial cells to AA induces a pro-fibrotic response via the c-Jun amino terminal kinase (JNK) signalling pathway. This study investigated the in vivo role of the JNK pathway in mouse models of AA-induced acute and chronic kidney injury. The effect of JNK inhibitor (CC-930) treatment was assessed in acute (day 3) and chronic (day 22) models of AA administration. In the acute model, CC-930 treatment significantly inhibited JNK signalling and gave protection from AA-induced renal function impairment and tubular cell damage: this was associated with reduced macrophage infiltration and expression of pro-inflammatory molecules. In the chronic model, CC-930 treatment significantly inhibited JNK signalling, but did not affect AA-induced renal function impairment, tubular cell damage or renal fibrosis, despite a significant reduction in the macrophage pro-inflammatory response. In conclusion, blockade of JNK signalling with CC-930 suppressed the acute effects of AA on tubular cell damage and renal function impairment, but was unable to protect the kidney against the effects of chronic AA exposure.